The Basic Design of Physical Education Instructional Model Based on Self-Regulated Learning Approach - Hendrayana, Yudy (EDUCARE, 2010)
ABSTRACT: The purpose of this research was to produce a basic design model of physical education instructional based on Self-Regulated Learning approach. The research was carried out using qualitative and quantitative methods on thirty Elementary School students (M = 11.2) and physical educators in Bandung city, as well as some experts from the School of Physical Education and Health Education of UPI (Indonesian University of Education) as samples. The data were gathered using the techniques of document analysis, questionnaires, observation, depth interview, and focus group discussion. The result of this research was a compilation of a basic design model of physical education instructional for Elementary School based on Self-Regulated Learning approach. Generally, physical education instructional condition in the Elementary School is good enough; it is indicated by the feasibility level of 68%. However, there are four primary problems faced by physical educators, such as instructional facility, equipment, time allocation, and students engaging in instructional activities. The instructional model has been used by Elementary School physical educators is sport education instructional model.KEY WORDS: Instructional model, physical education, self-regulated learning, Elementary School, and physical educators.Â Â About the Author: Dr. Yudy Hendrayana is a Lecturer at the School of Physical Education and Health Education UPI (Indonesian University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: yudy_hendrayana@upi.eduHow to cite this article? Hendrayana, Yudy. (2010). âThe Basic Design of Physical Education Instructional Model Based on Self-Regulated Learning Approachâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.35-44. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 29, 2010); Revised (July 30, 2010); and Published (August 17, 2010).